-6=14+x

Simple and best practice solution for -6=14+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=14+x equation:


Simplifying
-6 = 14 + x

Solving
-6 = 14 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + -1x = 14 + x + -1x

Combine like terms: x + -1x = 0
-6 + -1x = 14 + 0
-6 + -1x = 14

Add '6' to each side of the equation.
-6 + 6 + -1x = 14 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 14 + 6
-1x = 14 + 6

Combine like terms: 14 + 6 = 20
-1x = 20

Divide each side by '-1'.
x = -20

Simplifying
x = -20

See similar equations:

| 5=(-5a)+5 | | 5n^2-7n=4n^2-6 | | 5x-12x=32 | | B^2+33=12b+1 | | x^2+2a+(2a-1)=0e | | 6.2h+5-1.4h=4.8h+3 | | 12z-54=3z | | 5+42x=21x+11 | | 7x+26=2+10x | | (2x-5)+(2x+1)+72=180 | | -9=-4n+3-n^2 | | 2x+5x^2=100 | | X=15+.25x | | 42y+8=6 | | M^2+12=-8m | | 10/11X-4/11=8 | | -0.333X-0.666=1.333X-1 | | 2(n+2)(2n-5)=3n+7 | | 8+4-4a+a^2=8 | | 8+4-4a+4a+a^2=8 | | X+2=2x+-3 | | -40=-3x-x^2 | | 8x+32=10(x+2) | | 8+4m=9-7 | | 2x^2-17x+31=0 | | 8y+10=12y-10 | | 9y+10=12y-10 | | 42=-x^2-13x | | y[4]=0.7*y[4-1]+0.3*u[4-1] | | 3x^2+9=141 | | -2/3=1/2v-9/5 | | y[4]=0.7*y[n-1]+0.3*u[n-1] |

Equations solver categories